The Innovation of Augmented Reality Learning Media with Interactive Component Model to Improve Special Ability of Vocational Education Knowledge in the Digital Era - Tuwoso, Tuwoso; Putra, Andika Bagus Nur Rahma; Muhammad, Abd Kadir Bin (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This learning media innovation research aims to: (1) develop learning innovations of augmented reality learning media interactive tractor machine with 3D model; (2) test the feasibility level of the most recent advances learning media innovation; and (3) test the effectiveness of the most recent advances learning media innovations. The researcher selected to utilize the research and development (R&D) method for this research, and then used a quasi-experimental research method to examine the effectiveness of the development of learning media innovation. Two teams of professionals, e-learning media professionals and vocational education material professionals, work together to validate products. The study’s results include the following: First, two teams of validators determined that the augmented reality learning media with interactive 3D produced had a high attraction. Second, in the digital 4.0 era, augmented reality learning media with interactive 3D produced can help vocational students strengthen their specific abilities.